Low-Dose LPS Induces Tolerogenic Treg Skewing in Asthma - Ding, Fengxia; Liu, Bo; Niu, Chao; Wang, Ting; Wang, Yaping; Geng, Gang; Tian, Daiyin; Dai, Jihong; Fu, Zhou (Frontiers in Immunology, 2020)
The mechanism(s) underlying endotoxin tolerance in asthma remain elusive. As the endotoxin lipopolysaccharide (LPS) affects the expression of the regulatory T-cell (Treg)-suppressive glucocorticoid-induced tumor necrosis factor receptor ligand (GITRL) on antigen-presenting dendritic cells (DCs), we hypothesized that LPS-induced changes in DC GITRL expression may impact Treg-mediated T-helper (Th) cell suppression and the induction of endotoxin tolerance. Here, we propose a novel mechanism by which low-dose LPS inhalation in neonatal mice induces endotoxin tolerance, thereby offering protection from later asthma development. Three-day old wild-type and Toll-like receptor 4 (TLR4)-deficient neonatal mice were exposed to low-dose LPS (1 μg) intranasally for 10 consecutive days prior to ovalbumin (OVA)-induced asthma to better understand the tolerogenic mechanism(s) of low-dose LPS pre-exposure. In vivo findings were validated using in vitro co-culturing studies of primary CD11c+ DCs and CD4+ T-cells with or without low-dose LPS pre-exposure before OVA stimulation. Low-dose LPS pre-exposure upregulated the Treg response and downregulated pathogenic Th2 and Th17 responses through promoting apoptosis of Th2 and Th17 cells. Low-dose LPS pre-exposure downregulated DC GITRL expression and T-cell GITR expression. Artificial DC GITRL expression abrogated the tolerogenic Treg-skewing effect of low-dose LPS pre-exposure. Low-dose LPS pre-exposure inhibited TRIF/IRF3/IFNβ signaling and upregulated expression of tolerogenic TRIF/IRF3/IFNβ negative regulators in a TLR4-dependent manner. This tolerogenic DC GITRL downregulation was attributable to TRIF/IRF3/IFNβ signaling inhibition. Low-dose LPS pre-exposure produces tolerogenic Treg skewing in neonatal asthmatic mice, a phenomenon attributable to TLR4-dependent TRIF/IRF3/IFNβ-mediated DC GITRL downregulation.